The Influence of Management Control Systems on Business Innovation and Organisational Effectiveness in Indonesia - Ahmad Aminullah (Journal of Business Innovation and Accounting Research, 2025)
This study investigates the influence of Management Control Systems (MCS) on business innovation and organisational effectiveness within the Indonesian business context. Drawing upon the Four Levers of Control framework and enabling control design perspectives, this research examines how different control mechanisms—including beliefs, boundary, diagnostic, and interactive controls—affect innovation outcomes and organizational performance. Utilising a quantitative research methodology with survey instruments distributed across multiple Indonesian organisations, the study employs structural equation modelling and path analysis to test hypothesised relationships. The findings reveal that MCS implementation demonstrates significant positive correlations with both innovation capability and organizational effectiveness. Specifically, the enabling design of MCS positively influences the intensity of management control usage in innovation activities, while interactive control capabilities enhance technological innovation and firm performance through effective organizational learning. The results further indicate that cultural factors, leadership styles, and strategic alignment serve as critical determinants of successful MCS implementation in Indonesian organisations. This research contributes to the theoretical understanding of control-innovation dynamics and provides practical implications for Indonesian managers seeking to leverage control systems for enhanced organizational outcomes.